Enhancing violet photoluminescence of 2D perovskite thin films via swift cation doping and grain size reduction - Paphada Kaewurai (2020)
© 2018 The Japan Society of Applied Physics. Perovskite materials are emerging as suitable materials for low-cost, high efficiency optoelectronics. In this study, we reported the surface modification of 2D (PEA) 2 PbBr 4 for violet emission using PEG doping followed by a newly developed step called swift cation doping (SCD) where phenylethylammonium cations (PEA + ) in isopropanol (IPA) are abruptly applied during crystallization. 2D Perovskite doped with PEG using SCD resulted in smaller grain, smoother surface, higher film density, higher photoluminescence quantum efficiency, and longer average PL lifetime. These features are highly beneficial for photoluminescence application and can be easily applied to enhance other perovskite LED thin films.